Exploring teacher pedagogy, stages of concern and accessibility as determinants of technology adoption. Issue 2 (15th March 2018) - Burke, Paul F.; Schuck, Sandy; Aubusson, Peter; Kearney, Matthew; Frischknecht, Bart
Abstract: This research examines how the pedagogical orientations of teachers affect technology adoption in the classroom. At the same time, the authors account for the stage of concern that teachers are experiencing regarding the use of the technology, their access to the technology and the level of schooling at which they teach.The authors' investigation of these factors occurs in the context of a contemporary technology, the interactive whiteboard (IWB), in Australian schools. A structural equation model was estimated using a reflective measure of technology usage with antecedents in the form of pedagogical-oriented beliefs and best–worst scaling derived scores for a teacher's stage of concern regarding IWBs. Teachers with constructivist-oriented pedagogical beliefs were significantly more likely to use IWBs than transmission-oriented teachers. However, the strongest determinant of usage was whether the technology is immediately accessible or not.